Radiation-resistant X-ray scintillator film and preparation method thereof
By using the combination of Cs3Cu2I5 scintillator material and CsCu2I3 light conversion layer, combined with aluminum reflective film packaging and optimized process parameters, the long afterglow and irradiation damage problems of scintillator materials in the prior art are solved, and high resolution and radiation-resistant X-ray imaging effects are achieved.
Patent Information
- Application Number
- CN202411831107.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-11
AI Technical Summary
The existing CsI:T1 scintillator materials have long afterglow and irradiation damage problems in X-ray imaging, which affects image quality and diagnostic accuracy, and their emission wavelength does not match the response band of a-Si TFT, resulting in unsatisfactory luminescence efficiency and response performance.
Cs3Cu2I5 is used as the scintillator material, and the scintillator layer is prepared by static pressing sintering, and the CsCu2I3 light conversion layer is vapor-deposited on it. Combined with aluminum reflective film packaging, process parameters such as evaporation rate and temperature are optimized to improve the material's radiation resistance and light conversion efficiency.
It achieves high imaging resolution, low afterglow and radiation resistance stability, improves the luminous efficiency and response performance of scintillator materials, and is suitable for applications in the field of rapid detection.
Smart Images

Figure CN119800286A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of X-ray scintillator films, and in particular to a radiation-resistant X-ray scintillator film and a preparation method thereof. Background Art
[0002] At present, the scintillator material of commercial indirect X-ray flat-panel detectors is mainly cesium iodide doped thallium (CsI:Tl) material, which has high light yield, low detection limit and high X-ray imaging resolution. However, due to the long afterglow problem, CsI:Tl scintillator leads to the existence of delayed luminescence, which reduces the contrast and sensitivity of imaging; at the same time, in some rapid inspection scenarios such as security inspection and industrial casting and welding parts inspection, in order to improve the imaging quality, it is necessary to increase the X-ray dose to improve the radioluminescence response and penetration depth, which inevitably leads to the risk of radiation damage to CsI:Tl scintillator, especially in the case of long-term high-dose multiple imaging. The afterglow and radiation damage problems in X-ray imaging seriously affect the image quality and diagnostic accuracy. Therefore, it is urgent to develop scintillator materials with high imaging resolution, low afterglow and radiation stability to meet the application pain points in the field of rapid detection.
[0003] Research on hot copper-based halide perovskite materials, with Cs 3 Cu 2 I 5 As a new type of lead-free metal halide, the Cs-Cu-I system has attracted much scientific research attention due to its excellent X-ray luminescence performance, low afterglow, non-toxicity and excellent environmental stability. 3 Cu 2 I 5 The optimal emission wavelength of the detector is mainly in the blue light region, which has a poor match with the response band of the a-Si TFT (amorphous silicon thin film transistor) in the detector, resulting in unsatisfactory luminous efficiency and response performance when the two are combined. Therefore, it is urgent to study how to improve its light conversion performance with the existing a-Si TFT, which is the key to its industrial application. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the present invention provides a radiation-resistant X-ray scintillator film and a preparation method thereof.
[0005] To achieve the above object, the present invention provides a method for preparing a radiation-resistant X-ray scintillator film, which comprises the following steps:
[0006] (1) Preparation of scintillator layer raw materials: weigh CsI and CuI raw materials in a molar ratio of 3:2, grind and mix them, and then load them into a static pressure mold;
[0007] (2) Scintillator layer preparation: cold isostatic pressing to form the scintillator layer, followed by high temperature sintering to obtain Cs3 Cu 2 I 5 Scintillator layer;
[0008] (3) Preparation of light conversion layer evaporation: Using the prepared Cs 3 Cu 2 I 5 The scintillator layer is used as an evaporation substrate, and CsI and CuI raw materials are placed at the evaporation source position at a molar mass ratio of 1:2;
[0009] (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature, the rotation rate of the substrate is 1r / min-100r / min and the evaporation rate is gradually increased, and then cooled to room temperature to obtain CsCu 2 I 3 Light conversion layer;
[0010] (5) Scintillator film packaging: The lower surface of the light conversion layer is bonded to the a-Si TFT, and the Cs 3 Cu 2 I 5 The scintillator layer is encapsulated with an aluminum reflective film.
[0011] Preferably, the gradient increases the evaporation rate by sequentially increasing it in a gradient of 15r, and the time interval between each increase is 1-60min.
[0012] Preferably, the gradient evaporation rate is increased in sequence according to the gradient of 15 r / min, 30 r / min, and 45 r / min, and the time interval between each increase is 30 min.
[0013] Preferably, the cold isostatic pressing is performed by molding at a pressure of 5-30 MPa and then performing a cold isostatic pressing treatment at 100-200 MPa.
[0014] Preferably, the high temperature sintering is to vacuum sinter the formed green body at 350-450° C. for 2-24 hours, and then perform annealing at 100° C.-300° C. for 2-24 hours.
[0015] Preferably, the evaporation temperature is 350-500°C.
[0016] Preferably, the scintillator layer is replaced with Cs 3 Cu 2 Br 5 , Cs 3 Cu 2 Cl 5 , Cs 3 Cu 2 Cl x I5-x , Cs 3 Cu 2 Cl x Br 5-x , Cs 3 Cu 2 Br x I 5-x , Cs 5 Cu 3 Cl 6 I 2 , Gd 2 O 2 One or more of S, where X is in the range of 0≤X≤5.
[0017] Preferably, the vapor deposition substrate can be replaced by one or more of the already integrated TFTs including but not limited to amorphous silicon, IGZO, LTPS, and CMOS readout circuits.
[0018] Preferably, the packaging material can also be replaced by one or more of water and oxygen barrier film, PET, PI, PC, PMMA, PDMS, PTFE, photocuring adhesive, thermosetting adhesive, glass, ceramic, and metal sheet.
[0019] Preferably, the cleaning solvent can be one or a mixture of ethanol, isopropanol, n-butanol, n-hexane, ethyl acetate, methyl acetate, methyl formate, acetone, mercaptoethanol, methyl thioglycolate, and acetonitrile.
[0020] The present invention also provides a radiation-resistant X-ray scintillator film obtained by the above preparation method.
[0021] The beneficial effects of the present invention are as follows:
[0022] 1. Introduce the light conversion layer to improve the luminescence conversion efficiency of the scintillator layer. It is also non-toxic and environmentally friendly.
[0023] 2. Use gradient rate evaporation process to evaporate CsCu with a certain orientation 2 I 3 Light conversion layer to improve resolution;
[0024] 3. The scintillator film obtained by the press-sintering preparation process exhibits excellent radiation resistance. The process is easy to scale up production and meet commercial application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 . A schematic diagram of the scintillator film structure prepared in the present invention;
[0026] Figure 2 . Cs prepared in Example 1 3 Cu2 I 5 Scanning electron microscope cross-section of the scintillator layer (a) and the light conversion layer CsCu 2 I 3 SEM cross-section (b);
[0027] Figure 3 . Add CsCu in Example 1 2 I 3 Cs before and after the light conversion layer 3 Cu 2 I 5 Scintillator layer emission spectrum comparison;
[0028] Figure 4 . The sintering temperature and time for Cs in Example 1 3 Cu 2 I 5 Influence of scintillator luminescence performance;
[0029] Figure 5 . The line pair card resolution of the scintillator film deposited in Example 1 connected to the detector under X-ray imaging;
[0030] Figure 6 Mouse imaging under X-ray after the scintillator film deposited in Example 1 is connected to the detector;
[0031] Figure 7 . Photoconversion layer CsCu prepared at different rates 2 I 3 Scanning electron microscope cross-sectional views; wherein Figure (a) corresponds to Example 3, Figure (b) corresponds to Example 4, and Figure (c) corresponds to Example 5;
[0032] Figure 8 . Add CsCu in Comparative Example 1 2 I 3 Comparison of emission spectra of the GOS scintillator layer before and after the light conversion layer;
[0033] Fig. 9 . Cs prepared by blade coating (a) and ultrasonic spraying (b) in Comparative Examples 3 and 4 3 Cu 2 I 5 Scanning electron microscope cross-section of the scintillator layer;
[0034] Fig.10 . Image contrast changes before and after irradiation. X-ray imaging of the marked part of the scintillator film tube prepared in Example 1 before (a) and after (b) irradiation; X-ray imaging of the marked part of the CsI:Tl scintillator tube in Comparative Example 2 before (c) and after (d) irradiation. DETAILED DESCRIPTION
[0035] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments.
[0036] The steps of the present invention are as follows:
[0037] (1) Preparation of scintillator layer raw materials: weigh a certain mass of CsI and CuI raw materials in a molar ratio of 3:2, grind and mix them, and then put them into a static pressure mold;
[0038] (2) Scintillator layer preparation: The scintillator layer is formed at a pressure of 5-30 MPa, and then subjected to cold isostatic pressing (CIP) at 100-200 MPa. The formed body is vacuum sintered at 350-450°C for 2-24 hours, and annealed at 100-300°C to promote grain boundary melting and adjust defects. After cooling to room temperature, Cs 3 Cu 2 I 5 Scintillator layer, tested thickness is 350μm;
[0039] (3) Preparation of light conversion layer evaporation: Using the prepared Cs 3 Cu 2 I 5 The scintillator layer is used as the evaporation substrate, and the surface is scrubbed with sticky paper and n-butanol to ensure that the substrate reaches the required cleanliness for evaporation. After drying, it is installed above the evaporation source. Then, CsI and CuI raw materials are placed in special crucibles with a molar mass ratio of 1:2, and installed at the designated evaporation source position.
[0040] (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature and evaporation rate. Keep the substrate rotating during the evaporation process, and cool down to room temperature after the evaporation is completed to obtain CsCu 2 I 3 The light conversion layer is removed to test the thickness of the light conversion layer;
[0041] (5) Scintillator film packaging and testing: The lower surface of the light conversion layer is bonded to the a-Si TFT, and the Cs 3 Cu 2 I 5 The scintillator layer is encapsulated with an aluminum reflective film and then connected to an X-ray flat-panel detector for line-to-card resolution testing and radiation resistance testing.
[0042] Embodiment 1
[0043] (1) Preparation of scintillator layer raw materials: 90 mmol of CsI and 60 mmol of CuI raw materials were weighed in a molar ratio of 3:2, respectively, put into a crucible, grind and mix, and then put into a static pressure mold;
[0044] (2) Scintillator layer preparation: The scintillator layer was formed under a pressure of 10 MPa, and then cold isostatic pressing was performed at 200 MPa. The formed body was vacuum sintered at 375°C for 12 hours, and annealed at 200°C for 2 hours. After cooling to room temperature, Cs 3 Cu 2 I 5 Scintillator layer, tested thickness is 350μm;
[0045] (3) Preparation of light conversion layer evaporation: Using the prepared Cs 3 Cu 2 I 5 The scintillator layer is used as the evaporation substrate, and the surface is scrubbed with sticky paper and n-butanol to ensure that the substrate reaches the required cleanliness for evaporation. After drying, it is installed above the evaporation source. Then, 20 mmol of CsI and 40 mmol of CuI are weighed in a molar mass ratio of 1:2, respectively, and put into a special crucible, and installed at the designated evaporation source position;
[0046] (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature to 450 ° C. During the evaporation process, the substrate speed was increased from 15r / min-30r / min-45r / min, with a time interval of 30min. After the evaporation was completed and the temperature was cooled to room temperature, CsCu 2 I 3 Light conversion layer, remove and test the light conversion layer thickness of 50μm;
[0047] (5) Scintillator packaging and testing: The lower surface of the light conversion layer is bonded to an a-Si TFT (pixel size: 125 μm), and the upper surface of the Cs 3 Cu 2 I 5 The scintillator layer is encapsulated with an aluminum reflective film and connected to an X-ray flat-panel detector for line-to-card resolution test and radiation resistance test. The radiation resistance test involves irradiating the scintillator film with a large dose of 150KV, 1mA, and 6s, and then testing the image difference under mild conditions of 70KV, 1mA, and 125ms.
[0048] Embodiment 2
[0049] The preparation process is the same as that of Example 1, except that in steps (3) and (4), the substrate used for evaporation is a-Si TFT (pixel size: 125 μm). In the packaging process of step (5), Cs 3 Cu 2 I 5 The scintillator layer and the aluminum reflective film are bonded to the 50μm thick CsCu 2 I3 The light conversion layer is on top of the a-Si TFT.
[0050] Embodiment 3
[0051] The preparation process is the same as that of Example 1, except that in step (4), the rotation speed of the substrate is maintained at 30 r / min during the evaporation process.
[0052] Embodiment 4
[0053] The preparation process is the same as that of Example 1, except that in step (4), the rotation speed of the substrate is gradually reduced from 45 r / min-30 r / min-15 r / min during the evaporation process, with a time interval of 30 minutes.
[0054] Embodiment 5
[0055] The preparation process is the same as that of Example 1, except that in step (4), in order to further increase the thickness, the time interval is extended to 60 minutes, and the thickness of the prepared light conversion layer is 100 μm.
[0056] Embodiment 6
[0057] The preparation process is the same as that of Example 1, except that the preparation of the light conversion layer in step (3) and step (4) is omitted. 3 Cu 2 I 5 The scintillator layer undergoes packaging testing.
[0058] Comparative Example 1
[0059] (1) Scintillator layer preparation: Purchase commercially available standard GOS (Gd 2 O 2 S) scintillator, thickness 350 μm;
[0060] (2) Preparation for evaporation of the light conversion layer: Use the GOS scintillator layer as the evaporation substrate, and scrub the surface with sticky paper and n-butanol to ensure that the substrate reaches the cleanliness required for evaporation. After drying, install it above the evaporation source. Then, weigh 20 mmol of CsI and 40 mmol of CuI raw materials at a molar mass ratio of 1:2, respectively, put them into a special crucible, and install it at the designated evaporation source position;
[0061] (3) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature to 450 ° C. During the evaporation process, the substrate speed was increased from 15r / min-30r / min-45r / min, with a time interval of 30min. After the evaporation was completed and the temperature was cooled to room temperature, CsCu 2 I3 Light conversion layer, remove and test the light conversion layer thickness of 50μm;
[0062] (4) Scintillator packaging and testing: The lower surface of the photoconversion layer is bonded to the a-Si TFT (pixel size: 125 μm), and the upper surface is bonded to the GOS scintillator and then connected to the X-ray flat panel detector for line-to-card resolution test and radiation resistance test. The radiation resistance test is to irradiate the scintillator film with a large dose of 150 KV, 1 mA, and 6 s, and then use mild irradiation conditions of 70 KV, 1 mA, and 125 ms to test the image difference.
[0063] Comparative Example 2
[0064] (1) Scintillator layer preparation: Purchase commercially available standard CsI:Tl scintillator (with a reflective layer) with a thickness of 400 μm;
[0065] (2) The CsI:Tl scintillator was bonded to an a-Si TFT (pixel size: 125 μm), and then connected to an X-ray flat panel detector for line-to-card resolution test and radiation resistance test. The radiation resistance test was performed by irradiating the scintillator film with a large dose of 150 kV, 1 mA, and 6 s, and then using mild irradiation conditions of 70 kV, 1 mA, and 125 ms to test the image difference.
[0066] Comparative Example 3
[0067] (1) Preparation of scintillator layer raw materials: 90 mmol of CsI and 60 mmol of CuI raw materials were weighed in a molar ratio of 3:2 and placed in a ceramic ball mill;
[0068] (2) Scintillator layer preparation: Use a planetary ball mill to mill, add 10 mL of acetonitrile as a grinding aid, 600 μL of hypophosphorous acid as a stabilizer, and set the milling speed to 400 r / min for 20 hours. The saturated slurry after ball milling is prepared into a film by doctor blade coating, and annealed at 60°C for 2 hours. After cooling to room temperature, the film is removed to obtain Cs 3 Cu 2 I 5 Scintillator layer, tested thickness is 350μm;
[0069] (3) Preparation of light conversion layer evaporation: Using the prepared Cs 3 Cu 2 I 5 The scintillator layer is used as the evaporation substrate, and the surface is scrubbed with sticky paper and n-butanol to ensure that the substrate reaches the required cleanliness for evaporation. After drying, it is installed above the evaporation source. Then, 20 mmol of CsI and 40 mmol of CuI are weighed in a molar mass ratio of 1:2, respectively, and put into a special crucible, and installed at the designated evaporation source position;
[0070] (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature to 450 ° C. During the evaporation process, the substrate speed was increased from 15r / min-30r / min-45r / min, with a time interval of 30min. After the evaporation was completed and the temperature was cooled to room temperature, CsCu 2 I 3 Light conversion layer, remove and test the light conversion layer thickness of 50μm;
[0071] (5) Scintillator packaging and testing: The lower surface of the light conversion layer is bonded to an a-Si TFT (pixel size: 125 μm), and the upper surface of the Cs 3 Cu 2 I 5 The scintillator layer is encapsulated with an aluminum reflective film and connected to an X-ray flat-panel detector for line-to-card resolution test and radiation resistance test. The radiation resistance test involves irradiating the scintillator film with a large dose of 150KV, 1mA, and 6s, and then testing the image difference under mild conditions of 70KV, 1mA, and 125ms.
[0072] Comparative Example 4
[0073] (1) Preparation of scintillator layer raw materials: 90 mmol of CsI and 60 mmol of CuI raw materials were weighed in a molar ratio of 3:2 into a 300 mL beaker, and 180 mL of DMF solvent was added and stirred for 1 hour;
[0074] (2) Scintillator layer preparation: ultrasonic spraying was used for preparation, with an ultrasonic atomization frequency of 120 KHz, a carrier gas of nitrogen and a gas pressure of 0.05 MPa, a spraying liquid flow rate of 0.4 mL / min, and a substrate temperature of 120°C. After ultrasonic spraying, annealing was performed at 100°C for 2 hours, and Cs was obtained after cooling to room temperature. 3 Cu 2 I 5 Scintillator layer, tested thickness is 350μm;
[0075] (3) Preparation of light conversion layer evaporation: Using the prepared Cs 3 Cu 2 I 5 The scintillator layer is used as the evaporation substrate, and the surface is scrubbed with sticky paper and n-butanol to ensure that the substrate reaches the required cleanliness for evaporation. After drying, it is installed above the evaporation source. Then, 20 mmol of CsI and 40 mmol of CuI are weighed in a molar mass ratio of 1:2, respectively, and put into a special crucible, and installed at the designated evaporation source position;
[0076] (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4Pa, set the evaporation temperature to 450 ° C. During the evaporation process, the substrate speed was increased from 15r / min-30r / min-45r / min, with a time interval of 30min. After the evaporation was completed and the temperature was cooled to room temperature, CsCu 2 I 3 Light conversion layer, remove and test the light conversion layer thickness of 50μm;
[0077] (5) Scintillator packaging and testing: The lower surface of the light conversion layer is bonded to an a-Si TFT (pixel size: 125 μm), and the upper surface of the Cs 3 Cu 2 I 5 The scintillator layer is encapsulated with an aluminum reflective film and connected to an X-ray flat-panel detector for line-to-card resolution test and radiation resistance test. The radiation resistance test involves irradiating the scintillator film with a large dose of 150KV, 1mA, and 6s, and then testing the image difference under mild conditions of 70KV, 1mA, and 125ms.
[0078] Table 1 Luminous intensity, resolution and luminous intensity after irradiation of the vapor-deposited scintillator film and the readout circuit in each embodiment
[0079]
[0080]
[0081] The scintillator layer prepared by static pressing and sintering in the present invention is Figure 2 It can be seen that the morphology is uniform and dense, with few defects; after the introduction of the light conversion layer, on the one hand, excellent resolution is obtained through the process of increasing the rotation speed gradient, and the optimization of the substrate rotation speed promotes the uniformity of the film layer while inducing the subsequent growth of grains along the orientation of the underlying grains, showing vertical crystallization. Figure 2 As can be seen from the cross-sectional view in (b), the crystallization exhibits a certain columnar effect, which can reduce the refraction and scattering losses in the light transmission process, confirming the beneficial effect of the gradient rate enhancement process. Figure 7 The process results of constant speed and reduced speed in Examples 3 and 4 show that the bottom layer crystals have a certain vertical orientation from Figures a and b, and the orientation of the film grains disappears as the thickness increases; Figure c shows that the cross-sectional morphology has basically no orientation when the interval time is further extended in Example 5 to increase the thickness, resulting in a decrease in resolution; this further confirms that within a certain process range, the resolution gain effect of using a gradient rate enhancement process is achieved. Figure 5 and Figure 6 It can be seen that the scintillator film obtained in the first embodiment of the imaging has an excellent resolution, reaching 4.0LP / mm, and the imaging internal structure of the mouse is clear and the details are distinct.
[0082] On the other hand, the light conversion layer significantly improves the luminescence performance. As we all know, the optimal response band of a-Si TFT is around 550nm. Figure 3 It can be found that after the introduction of the light conversion film layer, the emission wavelength of the scintillator film layer moves toward the long-wave direction and the response of the TFT is enhanced, and the luminous intensity is increased by 30%, which well confirms the improvement of the luminous efficiency. Compared with Example 6 without adding the light conversion layer, the luminous intensity is significantly lower. The effects of replacing the substrate and using the GOS scintillator in Example 2 and Comparative Example 1 are equivalent to those in Example 1, and both have achieved significant luminescence improvement.
[0083] from Fig.10 It can be seen from Table 1 that the scintillator film of the present invention has excellent radiation resistance. After a large dose of irradiation, the image contrast and luminous intensity do not decrease significantly, while the image boundary is blurred when using the CsI:Tl scintillator film, and the radiation resistance is seriously reduced; in Comparative Example 2, the signal intensity and resolution of CsI:Tl are reduced due to the long afterglow problem, which is because Tl + The introduced impurity traps will more easily capture carriers and produce residual signals in the detector. These residual signals will interfere with subsequent X-ray detection, resulting in reduced contrast.
[0084] From the process comparison, it is found that the scintillator film layer in the comparative examples 3 and 4 using the scraping and spraying methods has many defects. Figure 8 It can be seen that the thick film layer prepared by scraping has more hole defects. The solvent escape and volatilization process inevitably cause more loose and porous structural defects, which are more likely to cause refraction and scattering of light conduction, resulting in a certain degree of performance degradation.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a radiation-resistant X-ray scintillator film, characterized in that: The following steps are included: (1) Preparation of scintillator layer raw materials: weigh CsI and CuI raw materials in a molar ratio of 3:2, grind and mix them, and then load them into a static pressure mold; (2) Preparation of scintillator layer: cold isostatic pressing is performed to form the scintillator layer, followed by high temperature sintering, and then the scintillator layer is obtained after cooling to room temperature; (3) Preparation for evaporation of the light conversion layer: Using the prepared Cs3Cu2I5 scintillator layer as the evaporation substrate, CsI and CuI raw materials are placed at the evaporation source position at a molar mass ratio of 1:2; (4) Photoconversion layer evaporation: Evacuate the evaporation furnace cavity to a vacuum degree of 5×10 -4 Pa, set the evaporation temperature, the rotation rate of the substrate is 1r / min-100r / min and the evaporation rate is gradually increased, and then the temperature is cooled to room temperature to obtain the CsCu2I3 light conversion layer; (5) Scintillator film packaging: The lower surface of the light conversion layer is bonded to the a-Si TFT, and the Cs3Cu2I5 scintillator layer on the upper surface is packaged with an aluminum reflective film.
2. The preparation method according to claim 1, characterized in that: The gradient increases the evaporation rate by a gradient of 15r, and the time interval of each increase is 1-60min.
3. The preparation method according to claim 1, characterized in that: The gradient evaporation rate is increased in sequence according to the gradient of 15 r / min, 30 r / min, and 45 r / min, and the time interval of each increase is 1-60 min.
4. The preparation method according to claim 1, characterized in that: The cold isostatic pressing is performed by molding at a pressure of 5-30 MPa and then performing a cold isostatic pressing treatment at a pressure of 100-200 MPa.
5. The preparation method according to claim 1, characterized in that: The high temperature sintering is to vacuum sinter the formed green body at 350-450° C. for 2-24 hours, and perform annealing at 100° C.-300° C. for 2-24 hours.
6. The preparation method according to claim 1, characterized in that: The evaporation temperature is 350-500°C.
7. The preparation method according to claim 1, characterized in that: The scintillator layer can be replaced by Cs3Cu2Br5, Cs3Cu2Cl5, Cs3Cu2Cl x I 5-x 、Cs3Cu2Cl x Br 5-x 、Cs3Cu2Br x I 5-x , Cs5Cu3Cl6I2, Gd2O2S; wherein the range of X is 0≤X≤5.
8. The preparation method according to claim 1, characterized in that: The vapor deposition substrate can be replaced by one or more of the already integrated TFTs including but not limited to amorphous silicon (a-Si), IGZO, LTPS, and CMOS readout circuits.
9. The preparation method according to claim 1, characterized in that: The packaging material is replaced with one or more of water and oxygen barrier film, PET, PI, PC, PMMA, PDMS, PTFE, photocuring adhesive, thermal curing adhesive, glass, ceramic, and metal sheet.
10. The radiation-resistant X-ray scintillator film obtained by the preparation method according to any one of claims 1 to 9.